PWE-126 Biodegradeable stents in the management of refractory non- malignant oesophageal strictures – an alternative to repeated endoscopic dilatations – a single centre experience. (17th June 2017) - Magee, C; Alzoubaidi, D; Banks, M; Sweis, R; Lovat, L; Haidry, R
Abstract : Introduction: The management of benign oesophageal strictures is classically via repeated endoscopic dilatations (ED). These require recurrent sessions over a short period of time. With each ED, there is a risk of perforation, and recurrent dilatations require frequent endoscopies, affecting the quality of life of patients. Self-expanding metal stents (SEMS) are another option but can result in stent migration, tissue in-growth and almost always require endoscopic removal after a period of time. We present a retrospective cohort study to assess if biodegradable (BD) stents (ELLA ltd) reduce the number of dilatations in patients with benign oesophageal strictures and to assess the length of time to next intervention following BD stent insertion. Method: All patients who had BD stents placed for benign strictures in our department between 2010–2016 were included. Following the insertion of the stents we analysed the time to next intervention (defined as ED or further stent insertion). We compared the number of EDs in the 12 weeks prior to stent insertion to the 12 weeks after. We noted any complications from the stents recorded on electronic patient records. Results: 34 BD stents were placed in our unit over 6 years in 16 patients. The mean age of patients was 56 years+/-16.9 years. 7 patients had peptic strictures, 4 patients had caustic strictures, 3 had radiation induced strictures and 2 had post-surgical anastomotic strictures. The mean length of stricture was 4.9 cm (+/-2.5). When a BD stent was inserted for the first time in a patient there was a significant reduction in the mean number of dilatations in the 12 weeks before BD stent insertion vs the 12 weeks after stent insertion. 3.16+/-1.8 dilatations vs 0.38+/-0.5 dilatations, p<0.005. The median time to intervention was 12 weeks (IQR:8–16.5). Kaplan-Meier statistics predict that at 12 weeks 55% of patients did not require re-intervention and at 18 weeks 22% of patients did not require intervention. Of the 34 stents, 2 (6.3%) developed oesophagitis, there were 2 (6.3%) blocked stents which were endoscopically resolved, and 2 (6.3%) patients developed severe pain. 1 patient developed an aorto-oeosphageal fistula requiring surgery 3 weeks post stent insertion. There was 1 stent migration. Conclusion: In our series the use of BD stents in well-selected non-malignant oesophageal strictures appears to reduce the number of EDs patients require in the 12 weeks after insertion compared to the 12 weeks prior. The time to next intervention would appear to be acceptable for most patients. However, some patients do not tolerate the stents, and one patient had the severe complication of an aorto-oeosphageal fistula. Disclosure of Interest: None Declared